PROMOTING CHARACTER EDUCATION THROUGH MARSIURUPAN VALUES - Rahmansyah, Habib; Pricilia, Gabby Maureen (Institut Pendidikan Tapanuli Selatan, 2025)
The purpose of this study is to outline how character education is impacted by the marsiurupan tradition’s local wisdom values in the Angkola marriage rite. Oral tradition known as marsiurupan is practiced in two contexts: happiness (siriaon) and sadness (siluluton). The marriage ceremony is a happy occasion for the Angkola people. Activities in the marsiurupan tradition during the wedding ceremony have principles derived from indigenous wisdom that aid in character development. A qualitative descriptive approach was adopted in this study. Participant observation is used to gather data, which is subsequently examined via qualitative data analysis. Based on the research, the findings indicate that the activities carried out, beginning with marpege-pege, pajongjong los, mamasu dahanon, mangkubak sibodak, and mardangdang, reflect the numerous local wisdom values found in the marsiurupan tradition.